Interactive calculation and verification of balanced fault currents - Khor Wei Wei (Universiti Malaysia Perlis, 2009)
In this paper a balanced short circuit analysis is performed on a simple power system using two recognized international standards (ANSI/IEEE C37.010.1979 and IEC 909 Standards). The ANSI standards performed using impedance-based calculations. It currently applies to equipment rating values include C37.010 for systems 1000 V and above. The IEC 909 Standard (1988) is derivative work taken from German Verband Deutscher Electrotechniker (VDE) Standard. This standard current-based calculation applies to all voltages up to 230 kV operating at nominal frequency (50 or 60 Hz). Both the ANSI and the IEC standards for short-circuit currents calculation procedures were developed to provide conservative results. For verification, comparisons are made between the values calculated with the IEC and appropriate ANSI/IEEE Standards.